Providing an Online Space for Interaction and Co-reflection during International Modules for LESLLA Practitioners: How Research(ers) can Serve LESLLA Teachers - Malessa, Eva; Young-Scholten, Martha (United States, 2025)
Many LESLLA practioners face challenges in participating in professional training and development courses. In this paper, we first discuss potential barriers they face in gaining access to relevant training and development. We then explore the benefits of remote professional training development by describing EU-Speak online modules (courses), which have been running since 2015 and have attracted the worldwide interest of teachers and tutors. EU-Speak modules provide an online space for interaction and co-reflection for LESLLA practioners and are an alternative to in-person training and development. Based on practioner-participants’ feedback and comments, we consider whether these affordable and relatively short (six-week) online modules can provide a stimulating space for participants to engage with each other and benefit from training and development. Participants’ comments show they can, along with emphasizing the need and necessity for training and development grounded in evidence-based research on adult late literacy development in a second language which the modules provide
Literacy Education and Second Language Learning for Adults (LESLLA): Proceedings of the 19th Annual LESLLA Symposium